KAJIAN PENGUSAHAAN BANDAR UDARA DI INDONESIA - Kusdian, R. Didin (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
In this time by the 21st century is growing increasing opportunities for non-governmental parties to play a role in the provision of public services and infrastructure management. In the air transport sector, since the year of 2000 all over the world have different frame mapped the non-government involvement in the provision and management of services about the airport. Indonesia has impose a Law No. 1 Year 2009 about Airline, where his message is one of separating contentgovernment and about the airport operator. Having applied for almost 5 years, yet fully aspects of involvement and participation of non-government parties to develop and run. It is an explanation of a more operational nature in the form of guidelines that govern more detail, as the elaboration of the content of the Law No. 1 Year 2009 About Airlines, specifically about the bodies in  airport enterprises.